Alignment of the initial phase during multiple-wavelength switching in microscopic interferometry. (July 2019) - Zhai, Zhongsheng; Zhang, Yanhong; Wang, Xuanze; Dong, Zhengqiong; Cheng, Zhuang; Lv, Qinghua; Su, Yuehong
Graphical abstract: Highlights: A phase shift method to drive the PZT by a zigzag with fallback path is proposed. The driving method can overcome the hysteresis and creep behavior of the PZT. It can reduce the phase shifting time and the driving cost of the PZT. The alignment errors are less than 0.018 rad. Abstract: Surface morphology measurement based on multiple wavelengths interferometric theory has been widely used, and the alignment error of initial phase of different wavelengths can influence the measurement accuracy. A phase shift method to drive the piezoelectric transducer (PZT) by zigzag with a fallback path is proposed, which can overcome the hysteresis and creep behavior of the PZT before switching to different wavelengths. The ellipse fitting and unwrapping algorithms are applied to extract phase-shifts from interferograms. The starting points of different wavelengths are aligned according to the displacement and movement direction of PZT. The experimental results show that the presented method can improve the aligned accuracy of the initial position during multiple-wavelength microscopic interferometry measurement.